Designing Resilient Hybrid Data Centers: Multi-Cloud Integration with Edge Computing for Improved Redundancy - Sreerangapuri, Ashok (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
As organizations adopt multi-cloud strategies to enhance operational agility, the integration of edge computing is emerging as a critical solution to address latency and redundancy challenges. This paper explores the architecture and design principles of hybrid data centers that seamlessly integrate cloud resources with edge nodes. It highlights the key considerations for ensuring redundancy, performance, and data sovereignty while managing distributed workloads. The study provides real-world case examples of hybrid data center deployments across different sectors, focusing on the role of software-defined networking (SDN) and network function virtualization (NFV). Furthermore, the paper identifies best practices and technological trends driving the adoption of hybrid architectures, including disaster recovery strategies, workload orchestration, and cross-platform security frameworks.